The impact of neglected tropical diseases on women and girl refugees: A call for increased awareness and strategic intervention - Duffey, Megan M.; Patel, Tulsi; Koukaz, Yasmine; Sepulveda, Theresa; Barbour, Kelli; Fredricks, Karla; Weatherhead, Jill E. (Frontiers in Tropical Diseases, 2022)
As the number of forcibly displaced women and girls increases, it becomes ever important to recognize the negative health impacts of being displaced. Women and girl refugees are disproportionately affected by sexual and gender-based violence and mental health concerns. In addition to these health concerns in women, crowding and lack of clean water in refugee camps leads to the spread of infectious diseases in general. Neglected tropical diseases (NTDs) are infectious diseases of poverty found in tropical areas, and longstanding infections lead to significant morbidity. Particularly for women, these diseases can impact fertility, chronic disease in pregnancy, and social stigma. Despite being a high-risk group, there are minimal data on the impact of NTDs on the health of Women and girl refugees. Diseases such as schistosomiasis, soil-transmitted helminth infections, strongyloidiasis, and leishmaniasis have all been shown to affect Women and girl refugees, but the majority of these data describe NTDs in this population only after resettlement. Access to medical care with providers that are knowledgeable about NTDs while in situations of displacement as well as after third-country resettlement is crucial to their timely diagnosis and treatment to prevent longstanding sequalae. More studies in this at-risk population are needed to understand the extent of this issue and begin to work towards lasting, equitable healthcare.